1994
DOI: 10.1128/mcb.14.9.6153
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of an E-box-binding repressor by basic helix-loop-helix proteins: implications for B-cell specificity of the immunoglobulin heavy-chain enhancer.

Abstract: The activity of the immunoglobulin heavy-chain (IgH) enhancer is restricted to B cells, although it binds both B-cell-restricted and ubiquitous transcription factors. Activation of the enhancer in non-B cells upon overexpression of the basic helix-loop-helix (bHLH) protein E2A appears to be mediated not only by the binding of E2A to its cognate E box but also by the resulting displacement of a repressor from that same site.We have identified a "two-handed" zinc finger protein, denoted ZEB, the DNA-binding spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
197
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(201 citation statements)
references
References 37 publications
3
197
0
1
Order By: Relevance
“…6,7 Although studies on ZEB1 focus mostly on its roles in epithelial-mesenchymal transition and metastasis, it is becoming evident that ZEB1 is also critical in the development of hematopoietic cells, including both B cells and T cells. For the B-lineage, ZEB1 may inhibit BCL6, the master transcription factor for the formation of germinal center B cells, 8 and is required for the normal development of marginal zone B cells and the production of immunoglobulin M. 9,10 Consistent with these data, overexpression of ZEB1 induces a more aggressive behavior of diffuse large B-cell lymphoma of the lymph nodes. 11 For the T-lineage, ZEB1 regulates T-cell development.…”
mentioning
confidence: 62%
“…6,7 Although studies on ZEB1 focus mostly on its roles in epithelial-mesenchymal transition and metastasis, it is becoming evident that ZEB1 is also critical in the development of hematopoietic cells, including both B cells and T cells. For the B-lineage, ZEB1 may inhibit BCL6, the master transcription factor for the formation of germinal center B cells, 8 and is required for the normal development of marginal zone B cells and the production of immunoglobulin M. 9,10 Consistent with these data, overexpression of ZEB1 induces a more aggressive behavior of diffuse large B-cell lymphoma of the lymph nodes. 11 For the T-lineage, ZEB1 regulates T-cell development.…”
mentioning
confidence: 62%
“…This zinc-finger transcription factor was initially identified as a transcriptional repressor of the immunoglobulin heavy chain enhancer in B-cells, acting through E-boxes (Genetta et al, 1994). Zeb1 can also bind the CDH1 promoter, thereby repressing its transcription and deregulating the epithelial phenotype of breast cancer cells (Eger et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…SpeciÂźc mutations in the prothymosin-a gene allow activation by TFE-3; similarly, mutations in the IgH enhancer allow activation by TFE-3 in non B-cells, demonstrating that TFE-3 is actively prevented from activating these genes in vivo (Desbarats et al, 1996;Genetta et al, 1994). We now demonstrate that DNA binding by USF is required for inhibiting transactiva-tion by TFE-3 in vivo.…”
Section: Introductionmentioning
confidence: 61%
“…Previous work has shown that ectopic expression of TFE-3 failed to activate the IgH or prothymosin-a enhancers; in both cases, a mutation in a second E-box element close to the TFE-3 binding site relieved the restriction, suggesting that factors binding to these elements actively prevent transcriptional activation by TFE-3 (Desbarats et al, 1996;Genetta et al, 1994) (Figure 1a). In order to test whether this restriction targets the transcriptional activation domain of TFE-3, we generated a chimeric protein that carries the transactivation domain of the viral Vp16 protein and a nuclear localization signal of SV40 large T antigen fused to the open reading frame of TFE-3 (Figure 1b).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation